Current concepts and a review of whose at risk - Hopkins, Mary-Lou (Operating Room Nurses Association of Canada Journal, 1987)
There are a number of risk factors operating room nurses and related 0.Fl. personnel should be con- stantly aware of. In the following submission, risk fac- tors associated with the operating room nursing pro- fession will be divided into the following categories for discussion: physical toxins radiation infectious agents burnout